Domestic violence: a comparative study of the law in Malaysia and India / Isabilla Najah Zaini ...[et al.] - Zaini, Isabilla Najah; Zainuddin, Mariani; Bunyamin, Nur Amalina; Faris, Siti Fariza (2009)
This research is about the law governing domestic violence in Malaysia and India. Reference and comparison are made between the relevant laws in both countries. The relevant law that been referred to were the Domestic Violence Act 1994, The Protection of Women from Domestic Violence Act 2005, the Indian Penal Code and Malaysian Penal Code. Cases were also been referred to illustrate the effectiveness of the law. Chapter one will introduce the concept of domestic violence, while, chapter two is the literature review. Chapter three and chapter four are chapters on the relevant law governing the domestic violence in India and Malaysia. Next, chapter five which stating the findings based on the legal chapters. Last but not least is chapter six which is the final chapter that states some recommendations on how to improve the law. This research project is set out to examine the protection provided to the victims and also the punishment imposed on the offenders of domestic violence in both countries. From this research there are some loopholes found in our law with regard this matter. Therefore some suggestions and recommendation has been made in order to make our law more effective or "the teeth that can bite".